Facies, geometry and growth phases of the Valdorria carbonate platform (Pennsylvanian, northern Spain). Issue 1 (17th August 2015) - Chesnel, Valentin; Samankassou, Elias; Merino‐Tomé, Óscar; Fernández, Luis Pedro; Villa, Elisa
Abstract: The 14 km wide Valdorria outcrop (Pennsylvanian, northern Spain) is one of the few examples of entirely exposed flat‐topped and high‐relief carbonate platforms reported in the fossil rock record. Laterally and vertically traceable stratal patterns expose three phases of growth. Phase I is a 430 m thick platform to slope succession that prograded over 6 km, and is dated as Early Bashkirian (Akavasian–Askynbashian). Phase II aggraded and prograded, exhibiting 180 m thickness of cyclical platform top deposits, dated as Late Bashkirian (Asatauian). Phase III is a mound‐shape structure that developed over the platform top of Phase II as a new phase of platform nucleation. It is 535 m thick and 2 km wide, and dated as Late Bashkirian (Asatauian–Transition interval). The observed changes of growth styles during platform evolution, from a prograding to an aggrading–prograding system, and a rapid aggradational phase, are inferred to be controlled by flexural subsidence in the active Cantabrian foreland basin, at the Variscan orogenic front. The metre‐scale shallowing‐upward cycles of the platform top are most probably due to glacioeustasy, as evidenced by well‐recorded subaerial exposure surfaces superimposed on subtidal deposits, and by a stratal pattern recurrent in a short interval of about 160 kyr. Observations of outcropping Bashkirian cyclothems in an isolated carbonate system, devoid of siliciclastic input, are relevant for a better understanding of the impact of high‐frequency sea‐level fluctuations on the carbonate factory. Moreover, progradation of the platform margin during Phase I reaches a rate of 2500 m/Myr, and 1810 m/Myr during Phase II; rates that are high when compared to other Pennsylvanian examples. The aggradation rate of 447 m/Myr calculated for the Late Bashkirian–Transition interval (Phases II and III; uncorrected for compaction, missing beats and erosion) is uncommonly high in comparison to coeval Pennsylvanian examples. The platform exhibits a self‐nourishing prograding microbial boundstone‐dominated slope. Thus, the slope‐shedding model applies well to Valdorria. However, Phase II recorded eustatic variations able to inhibit the slope microbial boundstone factory during low sea‐level stands; this is marked by common slope red‐stained breccias synchronous to platform top subaerial exposure phases. Contrarily, periods of relative high sea‐level and rapid subsidence in Phase III registered a greater development of cemented microbial boundstone. These observed, partly opposing relationships of sea‐level stands, shedding modes and slope architecture provide an improvement of the currently used slope‐shedding model. The overall architecture of the Valdorria outcrop compares well with that of other contemporaneous platforms, such as Sierra del Cuera and Bolshoi Karatau. Valdorria shares the high‐relief and flat‐topped, steep slopes, cyclothemic patterns and occurrence of karst features with the Pricaspian Basin platforms (Tengiz, Karachaganak and Kashagan), with minor variations in facies distribution of the internal platform. Furthermore, the continuous seismic‐scale outcrop of Valdorria, together with its isolated setting and asymmetrical growth, makes it a very good candidate for potential subsurface analogues of hydrocarbon‐bearing systems.